Social (Re)construction of a Local Community After Massive Traumatization - Ajduković, Dean (Array, 2005)
The role of social contexts of traumatisation and healing has profound consequences for social reconstruction and reconciliation of communities that have been exposed to upheaval and organized violence. The social contexts in which mass traumatisation of thousands of people occur and in which their recovery should progress have qualities that distinguish them in important ways from individualized traumatisation in which a person is a victim of an isolated violent attack, rape or a traffic accident. Massive violence affects both individuals and the community, while after-effects extend far beyond the trauma symptoms, both in time and psychosocial implications. Effective community-based interventions can help facilitate psychosocial reconstruction of the communities, decrease social tensions among groups that have been involved in a conflict, provide treatment for the most traumatized individuals and work towards re-connecting community members. The individual recovery from trauma and community social reconstruction are parallel, interwoven and non-linear processes. We see three simultaneous processes that comprise community social reconstruction that can lead to favorable outcomes at different levels: recovery from losses and exposure to violence ; establishing new social norms and tolerance ; empowerment of players of community change.